Zinc, iron and phytic acid levels of some popular foods consumed by rural children in Sri Lanka - Karunaratne, A.M.; Amerasinghe, Priyanie H.; Ramanujam, V.M.S.; Sandstead, H.H.; Perera, P.A.J. (2008)
Zinc (Zn) and iron (Fe) deficiencies may prevail in populations dependent on cereal-based diets containing few animal products. The contribution of Zn and Fe from foods of preschool children of a hill country village in Sri Lanka, is discussed as it is known that the presence of phytic acid (PA) in the diet limits bioavailability of micronutrients. The Zn, Fe and PA contents of cereal-based (rice or wheat flour) composite meals (n ? 12), wheat flour-based products (n ? 5), pulses used as staples, snacks or accompaniments (n ? 6) and other miscellaneous accompaniments (n ? 4) were determined. Additionally, 20 rice and 3 paddy varieties consumed were also analysed. Although the Zn and Fe levels were reasonable in the composite meals, the PA to Zn molar ratios (5-43) were relatively high, in a majority of meals. Composite meals containing wheat flour (refined) had lower PA levels (o6 mg/ 100 g) in the absence of pulses and scraped coconut, than rice meals. All rice varieties were partially polished but the A to Zn molar ratios varied. The major contributors of PA appeared to be soy-textured vegetable protein, all types of jak fruit and scraped coconut kernel. Potable water was a poor source of Zn and Fe. These diets could potentially lead to marginal Zn and Fe deficiencies, and dietary diversification and counselling would be beneficial.